2022
DOI: 10.3390/nu14153102
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Effects of Black Soybean Peptide on Oxidative Stress Injury Induced by Lead in PC12 Cells via Keap1/Nrf2/TXNIP Signaling Pathway

Abstract: Many researchers have found that Pb exposure can cause oxidative stress damage to the body’s tissue. Black soybean peptide (BSP) has a variety of physiological functions, especially in terms of oxidative stress. Nevertheless, the mitigation function of BSPs on Pb-induced oxidative stress damage in PC12 cells has not been clearly defined. In this study, cell viability was detected by CCK8. Oxidative stress indicators, such as ROS, GSH/GSSG, MDA, SOD, CAT, GPx, and GR, were tested with biochemical kit. Protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It has been reported that hydrogen peroxide-induced oxidative stress in cells causes an increase in the levels of ROS and MDA and a decrease in SOD and GSH ( 42 ). Vitamin C in combination with vitamin E has been reported to alleviate oxidative stress caused by lead exposure by increasing the levels of SOD, CAT, and GSH-Px ( 43 , 44 ). The present study found that lead exposure significantly increased MDA levels and significantly decreased SOD, GSH, and GSH-Px simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hydrogen peroxide-induced oxidative stress in cells causes an increase in the levels of ROS and MDA and a decrease in SOD and GSH ( 42 ). Vitamin C in combination with vitamin E has been reported to alleviate oxidative stress caused by lead exposure by increasing the levels of SOD, CAT, and GSH-Px ( 43 , 44 ). The present study found that lead exposure significantly increased MDA levels and significantly decreased SOD, GSH, and GSH-Px simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Crude polysaccharides were extracted from BS exhibited antioxidant effects, although the DPPH and superoxide anion free radicals of crude polysaccharides (72.22% and 77.88%, respectively) were slightly lower than those of the V C control (97.91% and 97.56%, respectively; J. Liu, Wen, Kan, Zhang, et al., 2015). Many studies have claimed that BS peptides exhibit antioxidant effects by activating the Keap1/Nrf2 signaling pathway (Cui et al., 2022; N. Li et al., 2022; J. Ren et al., 2021; Y. H. Wu et al., 2014). Particularly, Y. H. Wu et al.…”
Section: Health Benefitsmentioning
confidence: 99%
“…Typically, the same analysis used to detect cell viability over a specified period can reflect cell proliferation. Previous research revealed that the PC12 cell, a rat pheochromocytoma cell line, which has been widely used as a cell model in studies of neurodegenerative diseases for the PC12 cell, has similar neuronal characteristics, physiology, and pathology of the nerve cells [38]. PC12 cells (1 × 10 5 cells/mL) were treated with different concentrations (0-800 µg/mL) of BR fractions for 24 h at 37 • C after normal culture for 24 h to observe toxicity.…”
Section: Cytoprotective Activity On Pc12 Cell Viabilitymentioning
confidence: 99%